Pemanfaatan Jerami Padi Dan Serbuk Kayu Menjadi Biopelet Sebagai Bahan Bakar Alternatif - Najwa Faizah Azima Buhang; Aditia Ginantaka; Teguh Wikan Widodo; Ridwan Rachmat (JURNAL AGROINDUSTRI HALAL, 2024)
Most human activities use fossil energy to meet their energy needs. Fossil energy is limited in quantity and non-renewable in nature, raising concerns that it may no longer sustain future energy demands. Bio-pellets are an alternative fuel that can address the scarcity of stove fuels such as kerosene and gas. Rice straw is one of the potential biomass materials for bio-pellet production due to its abundance and environmental sustainability. The addition of wood powder in bio-pellet manufacturing can increase calorific value and improve pellet energy efficiency. This research aims to find a bio-pellet formula combining rice straw and wood powder that complies with SNI 8021:2014. The method employed in this study is experimentation, involving the creation of three different bio-pellet compositions. The selection of the best bio-pellet is determined by analyzing the collected data using single-factor RAL in SPSS 24 software. The chosen bio-pellet formulation in this study is KJ1 with a density of 1.457 g/cm3, moisture content of 9.076%, calorific value of 3,924.48 cal/g, and water boiling rate of 284 seconds.